The Impact of COVID-19 on the Finances of the Tourism Industry in Indonesia - HIDAYAT, Wastam Wahyu; HUSADHA, Cahyadi (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
This study aims to look at the impact of COVID 19 on tourism-related sectors, including the air transportation sector, hospitality accommodation providers, and food and beverage providers, in this study the data obtained is sourced from interviews, journals, newspapers, and other information that supports the fulfillment of this paper. After analysis from various data sources where the tourism sector is very impacted by COVID-19, especially the number of tourists, so that the reduced needs of hotels and food providers, even impact the workforce in the field of tourism, which resulted in revenue, economy and finances fell completely, therefore the government provided stimulus in the form of, Fiscal Stimulus Policy and Policy of the Ministry of Tourism and Creative Economy.